S대학 치위생과 실습실에 내원한 환자의 치아우식상태와 구강위생관리능력 구강건강행위 실태 - 김진; Jin Kim; 우희선; Hee Sun Woo; 정문희; Moon Hee Jung (Chiwisaeng gwahakoeji, 2009)
The purpose of this study was to examine the correlation of oral health behavior, oral health state and PHP in an effort to facilitate the promotion of oral health and improve oral health care. The subjects in this study were patients who got a scaling at the oral hygiene practice lab in the department of dental hygiene in S college dental clinic from September 5 to December 1, 2007. The collected data were analyzed with SPSS WIN 12.0 program. The findings of the study were as follows: 1. The younger patients had a smaller number of FT index, and the older patients excelled the younger ones in oral health behavior involving the use of oral hygiene supplies, regular visit to dental clinics and dietary control. 2. The patients got 2.62 out of possible five points on oral health behavior, which indicated that their oral health behavior wasn't good enough. Those whose oral health behavior was better had a smaller number of DT index and a larger number of FT index. A better oral health behavior led to a lower PHP index. 3. There was a negative(-) interrelationship between oral health behavior and DT index, and oral health behavior had a positive(+) correlation with FT index. The oral health behavior had a negative(-) correlation to PHP index, which showed that a better oral health behavior led to a lower PHP index. The above-mentioned findings seem to suggest that oral health behavior is one of integral factors to affect oral health status and PHP index, and the kind of oral health education that could change oral health care attitude should be provided during scaling practice after grasping the actual oral health behavior of patients. 본 연구는 구강건강행위와 구강건강상태, 구강위생관리능력과의 상호관계를 분석하여, 치과위생관리를 위한 기초자료를 제공하고자 2007년 9월 5일부터 12월 1일까지 S대학 치위생과 구강위생실습실을 내원한 스켈링 실습환자를 대상으로 실시하였으며, SPSS WIN 12.0 프로그램을 이용하여 분석하였다. 1. 연령이 낮을수록 우식경험처치치아의 수(FT index)가 높은 것으로 조사되었으며, 구강위생용품 영역, 정기적인 치과방문 영역, 식이조절 영역에서는 연령이 증가할수록 구강건강행위가 높은 것으로 조사되었다. 2. 대상자의 구강건강행위 정도는 5점 만점에서 2.62로 대체적으로 낮은 수준으로 조사되었으며, 잇솔질 영역에서는 '위아래로 치아를 닦고 잇몸과 혀도 닦는다', 구강위생용품 영역에서는 '구강양치액(가그린)을 사용 한다', 정기적인 치과방문 영역에서는 '아픈 경우 미루지 않고 치과에 방문 한다', 식이조절 영역에서는 '우식성식품 보다 청정식품을 섭취 한다', 교육 및 관심 영역에서는 '흡연이 구강건강에 좋지 않음을 교육받는 적이 있다'가 가장 높게 조사되었다. 3. 구강건강행위가 높을수록 우식경험미처치치아(DT index)의 수가 낮아지는 것으로 조사되었으며, 구강건강행위가 높을수록 우식경험처치치아의 수는 높은 것으로 조사되었다. 치면세마 실습실에 내원한 환자의 구강위생관리능력 수준을 분석한 결과 '양호' 25%, '보통' 36.3, 불량 30.4, 매우불량 8.3%로 조사되어 대부분의 환자들의 구강위생관리 능력이 불량한 것으로 조사되었으며, 구강건강행위가 높을수록 구강위생관리능력 지수는 낮아지는 것으로 조사되었다. 4. 구강건강행위와 우식경험미처치치아(DT index) 간에 음(-)의 상호관련성이 있는 것으로 분석되어, 구강건강행위가 높을수록 우식경험미처치치아(DT index)의 수는 낮아지는 것으로 조사되었다(p < .01). 구강건강행위와 우식경험처치치아(FT index) 간에 양(+)의 상호관련성이 있는 것으로 분석되어, 구강건강행위가 높을수록 우식경험처치치아(FT index) 수는 높아지는 것으로 조사되었다(p<.01). 구강건강행위와 구강위생관리능력 지수(PHP index) 간에 음(-)의 상호관련성을 보이고 있어 구강건강행위가 높을수록 구강위생관리능력 지수(PHP index)는 낮아지는 것으로 조사되었다(p < .01).